Evolution of Somite Compartmentalization: A View From Xenopus - Della Gaspera, Bruno; Weill, Laure; Chanoine, Christophe (Frontiers in Cell and Developmental Biology, 2022)
Somites are transitory metameric structures at the basis of the axial organization of vertebrate musculoskeletal system. During evolution, somites appear in the chordate phylum and evolve to compartmentalize mainly into the dermomyotome, the myotome and the sclerotome in vertebrates. In this review, we summarized the existing literature on somite compartmentalization in Xenopus and compare it with other anamniote and amniote vertebrates. We have also presented and discussed a model that describes the evolutionary history of somite compartmentalization from basal chordates to amniote vertebrates. We propose here that the ancestral organization of chordate somite, subdived into a lateral compartment of multipotent somitics cells (MSCs) and a medial ancestral myotome, evolves through two major transitions. From chordates to anamniote vertebrates, the cell potency of MSCs may have evolved to give rise to all new vertebrate compartments, i. e. the dermomyome, its hypaxial region and the sclerotome. From anamniote to amniote vertebrates, the lateral MSCs territory may expand to the whole somite at the expense of ancestral myotome probably to facilitate sclerotome formation. We propose that succesive modifications of the cell potenty of some type of embryonic progenitors could be one of major processes of the vertebrate evolution.